COMPARATIVE STUDY ON THE INCIDENCE OF BURNOUT'S SYNDROME AT PUBLIC AND PRIVATIVE SCHOOL'S PROFESSORS OF MARINGÁ-PR (Fiep Bulletin - online, 2013)
School has been considered now a day a business and the professor is just a worker that besides doing his pedagogic duties has to accomplish many other functions. This intensification of teachers' obligations is causing them conflicts; their time to study and actualizations is too short. Burnout is the used term to designate a chronic feeling of discouragement, apathy and depersonalization that affects professionals of many areas, especially from health and education areas. This syndrome is the result of emotional stress caused by the interaction with others. This present study aims to diagnose the presence, the causes, the incidences and the treatment of the Burnout Syndrome in professors of public and private schools. Therefore, descriptive procedures were used in a population composed by public and private schools teachers. Eighty two people were used in this study, of both genders. After the professor's selection a questionnaire developed by Maslach and Jackson (1981) was applied to identify the Burnout Syndrome. Of the eighty two professors studied, 18,29% presented symptoms of the syndrome, but in general terms the professors presented some symptom of Burnout. Most of the professors that presented the symptoms of the syndrome may be considered young (31 to 40 years) and had a relative short time of teaching in school (nine to sixteen years). In conclusion, younger professors and with short time of magistracy tend to develop the Burnout Syndrome. The cause of that can be due to the accumulation of business and also the pressure they suffered in their work environment.
Keywords: Burnout Syndrome; professor; teach